2016
DOI: 10.1002/uog.15814
|View full text |Cite
|
Sign up to set email alerts
|

Dydrogesteronevsprogesterone for luteal-phase support: systematic review and meta-analysis of randomized controlled trials

Abstract: Objectives To compare the effects of dydrogesterone and progesterone for luteal-phase support (LPS) in women undergoing assisted reproductive techniques (ART). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 39 publications
0
27
1
3
Order By: Relevance
“…Where a significant difference was observed, we determined the number needed to treat for an additional beneficial (NNTB) or harmful (NNTH) outcome. The random-effects model was chosen because the true effect size should not be assumed to be the same across studies; additionally, the random-effects model incorporates the observed heterogeneity among studies, obtaining more conservative CIs [14][15][16] . Heterogeneity was assessed by the I 2 statistic; wherever it was moderate (I 2 > 30%) or substantial (I 2 > 50%), we explored the possible explanations by conducting subgroup analyses, sensitivity analyses and cumulative meta-analyses.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…Where a significant difference was observed, we determined the number needed to treat for an additional beneficial (NNTB) or harmful (NNTH) outcome. The random-effects model was chosen because the true effect size should not be assumed to be the same across studies; additionally, the random-effects model incorporates the observed heterogeneity among studies, obtaining more conservative CIs [14][15][16] . Heterogeneity was assessed by the I 2 statistic; wherever it was moderate (I 2 > 30%) or substantial (I 2 > 50%), we explored the possible explanations by conducting subgroup analyses, sensitivity analyses and cumulative meta-analyses.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…In a randomized study, a lower risk of preterm birth was associated with oral micronized progesterone than placebo [ 27 ]. Additionally, in a recent meta-analysis, oral dydrogesterone was as effective as vaginal progesterone for luteal phase support in assisted reproduction [ 28 ]. It has also been reported that intramuscular progesterone administration is associated with implantation, clinical pregnancy, and delivery rates that are comparable to those resulting from treatment with vaginal progesterone during stimulated IVF cycles [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of route of administration, progesterone used as LPS in our study was oral Dydrogesterone (10 mg twice daily). This route of use in the study was supported by systematic review and meta-analysis of RCT done by Barbosa et al who ended up in a conclusion that the use of oral dydrogesterone seems to be as effective as vaginal progesterone for LPS in ART cycles and appears to be better tolerated [21]; furthermore, oral route efficacy confirmed in IVF by Phase III-RCT that compares the efficacy, safety, and tolerability of oral dydrogesterone versus micronized vaginal progesterone for LPS [22]. Similar reports on equivalent efficacy were documented from RCTs in Iran and India [23,24].…”
Section: Discussionmentioning
confidence: 80%